The relationship between physical exercise and subjective well-being among Chinese junior high school students: A chain mediating model - Yao, Shu-Jun; Ma, Qi-Shuai; Liu, Chao; Cao, Da-Wei; Lyu, Teng; Guo, Ke-Lei (Frontiers in Psychology, 2023)
Objective: This study aims to help understand the mechanism behind the relationship between physical exercise and the subjective well-being among Chinese junior high school students, and it is of great significance for the intervention measures to improve the subjective well-being of junior high school students. Methods: Using stratified cluster sampling method, 1510 junior high school students (727 males and 783 females) were measured by physical exercise rating scale, perceived social support scale, physical exercise self-efficacy scale, and subjective well-being scale. For data analysis, Pearson’s correlation analysis, structural equation model test, and bias-corrected percentile Bootstrap method were carried out in turn. Results: Common method biases can be accepted in this study. (1)There is a positive correlation between physical exercise and subjective well-being, and physical exercise has a significant predictive effect on subjective well-being(β= 0.367，t=9.415，p＜0.01)；(2) Perceived social support partially mediated the relationship between physical exercise and subjective well-being (β=0.08, t=3.083, p<0.01), and its effect ratio is 78.047%; (3)Physical exercise self-efficacy plays a partial mediating role between physical exercise and subjective well-being(β=0.181, t=5.132, p<0.01), accounting for 50.632%; (4)The chain mediating effect of perceived social support and physical exercise self-efficacy was significant (the mediating effect value was 0.028), and the effect amount was 7.629%. Conclusion: (1) Physical exercise can significantly positively predict the subjective well-being of junior high school students; (2) Physical exercise can also indirectly affect the subjective well-being of junior high school students through the mediating effect of perceived social support and physical exercise self-efficacy. The intermediary effect includes three paths, namely, the individual intermediary effect of perceived social support and physical exercise self-efficacy and the chain intermediary effect of perceived social support physical exercise self-efficacy.